Effects of Cultured Cordycep militaris on Sexual Performance and Erectile Function in Streptozotocin-Induced Diabetic Male Rats. (16th November 2020) - Pohsa, Sureena; Hanchang, Wanthanee; Singpoonga, Nattapong; Chaiprasart, Peerasak; Taepavarapruk, Pornnarin
Abstract : Cordyceps militaris (CM), a valuable edible and medicinal fungus, has been used as traditional medicine to treat health conditions, as well as hyposexuality in Asian societies for over a century. Due to the high demand, several artificial cultivation methods have been developed for their biological activities. In this study, CM was cultured on medium that contained white rice and silkworm pupae, and the levels of cordycepin and adenosine, as well as its aphrodisiac effects in diabetes-induced erectile dysfunction (DIED), were evaluated. Diabetic rats were induced by streptozotocin (STZ) injection and administered orally with CM (0.1, 0.5, and 1.0 g/kg BW/day) for 3 weeks. Diabetic rats in negative and positive control groups received vehicle and sildenafil citrate (5 mg/kg), respectively. Results showed the changes in mating behaviour in which mount latency and intromission latency were significantly increased in diabetic rats, compared with the normal control group. Diabetic rats also showed a significant reduction in intracavernosal pressure (ICP) response to cavernous nerve stimulation, sperm count, testosterone level, penile nitric oxide synthase (NOS), and testicular superoxide dismutase (SOD) activities, when compared to the normal control group. Administration of CM (0.1, 0.5, and 1.0 g/kg BW/day) reversed the effects of diabetes on the mating behaviour, and the ICP responses to electrical stimulation. Moreover, the levels of penile NOS, testicular SOD activities, testosterone, and sperm count were significantly increased, and testicular malondialdehyde (MDA) levels were significantly decreased in these treated diabetic rats. Diabetic rats treated with sildenafil showed a significant induction in intromission frequency and NOS and SOD activities, as well as a marked increase in ICP responses. These results suggest that CCM exerts its aphrodisiac effect, possibly through activating testosterone production and suppressing oxidative stress to enhance erectile function in diabetic rats.